2012
DOI: 10.1111/j.1600-0447.2012.01913.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the diagnosed incidence of early onset schizophrenia over four decades

Abstract: In recent years, the diagnosed incidence of EOS has increased and the usual male excess has disappeared. The changes in IR could be a result of changes in the diagnostic system, increased awareness of early psychosis or a reflection of actual underlying incidence of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 39 publications
5
47
2
Order By: Relevance
“…It cannot be determined whether the increase in incidence represents an actual increase in the number of affected people as many factors influence the application of different diagnoses (Kjeldsen et al 2012). Therefore, our finding represents the diagnosed or treated incidence, which could either over-or underestimate the true incidence, depending on the diagnostic practices regarding the disorder (Kjeldsen et al 2012;Okkels et al 2013).…”
Section: Main Findingsmentioning
confidence: 71%
See 1 more Smart Citation
“…It cannot be determined whether the increase in incidence represents an actual increase in the number of affected people as many factors influence the application of different diagnoses (Kjeldsen et al 2012). Therefore, our finding represents the diagnosed or treated incidence, which could either over-or underestimate the true incidence, depending on the diagnostic practices regarding the disorder (Kjeldsen et al 2012;Okkels et al 2013).…”
Section: Main Findingsmentioning
confidence: 71%
“…Therefore, the number of patients with diagnoses other than ADHD is probably underestimated, as the patients registered with a diagnosis of ADHD at their latest contact could have received another diagnosis at their previous visits. Further, they could have other psychiatric disorders registered as auxiliary diagnoses and emergency room contacts, which were not included in this study due to a low validity (Okkels et al 2013). As the findings of this study are not being used to claim any causal correlation between ADHD and certain disorders, but rather to enlighten the stability of the diagnosis, the possible underestimation is acceptable.…”
Section: Strengths and Limitationsmentioning
confidence: 85%
“…Okkels et al estimated the incidence of early onset schizophrenia in Denmark using a nationwide, population-based, mental health register. Their findings suggest that the sex differential has narrowed over time and the usual male excess has disappeared in recent years (75). A comprehensive literature review focusing on gender differences in schizophrenia showed that no epidemiological studies have found a significant difference in males and females (76).…”
Section: Prevalence By Gendermentioning
confidence: 98%
“…We were unable to extrapolate our models to this age range, given the current absence of incidence data for this group in England. Data from Scandinavia suggest that the incidence of such 'early onset' psychoses is absolutely low, 29 although the rate may have increased over the last few decades, probably as a result of movement towards earlier detection. We were also unable to externally validate prediction models for people aged 36-64 years, because comparable observed incidence data were not available in our validation sample.…”
Section: Limitations and Future Developmentmentioning
confidence: 99%